2012
DOI: 10.5376/bt.2012.03.0004
|View full text |Cite
|
Sign up to set email alerts
|

Cry10Aa Protein is Highly Toxic to <i>Anthonomus grandis</i> Boheman (Coleoptera: Curculionidae), an Important Insect Pest in Brazilian Cotton Crop Fields

Abstract: The cry10Aa gene from the Brazilian Bacillus thuringiensis subsp israelensis S1804 strain was introduced into the genome of the baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV) in order to evaluate its expression in insect cells and its toxicity to A. grandis. The recombinant virus (vSyncry10Aa) was amplified in Trichoplusia ni (BTI-Tn5B1-4) cells and used to infect Spodoptera frugiperda larvae. Total extracts from S. frugiperda infected with the recombinant viruses were analyzed by SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Craveiro et al (2010) reported the efficient biological control of sugarcane giant borer caused by the Lepidopteran larvae Telchin licus licus (Castniidae) by variants of Cry1Ia toxins. Other studies reported the high toxicity of B. thuringiensis Cry protein towards Anthonomus grandis Boheman (Coleoptera: Curculionidae) (de Souza Aguiar et al, 2012) and towards Cylas puncticollis and Cylas brunneus (Coleoptera: Brentidae) (Ekobu et al, 2010).…”
Section: Insecticidal Activity Of B Thuringiensis Derived Biopesticidesmentioning
confidence: 98%
“…Craveiro et al (2010) reported the efficient biological control of sugarcane giant borer caused by the Lepidopteran larvae Telchin licus licus (Castniidae) by variants of Cry1Ia toxins. Other studies reported the high toxicity of B. thuringiensis Cry protein towards Anthonomus grandis Boheman (Coleoptera: Curculionidae) (de Souza Aguiar et al, 2012) and towards Cylas puncticollis and Cylas brunneus (Coleoptera: Brentidae) (Ekobu et al, 2010).…”
Section: Insecticidal Activity Of B Thuringiensis Derived Biopesticidesmentioning
confidence: 98%
“…Different chemical insecticides have been used for its control such as Calcium arsenate, dichloro-diphenyl-trichloroethane (DDT) and organophosphates. This insect pest is susceptible to several Cry proteins such as Cry1Ia, Cry8Ka, Cry10Aa and Cry22Aa [41][42][43][44]. ABC transporters as well as APN and CAD have been identified as binding proteins form Cry8Ea in H. parallela and H. oblita [45,46].…”
Section: Plos Onementioning
confidence: 99%
“…The colonies of A. aegypti and C. quinquefasciatus were established from insects collected from the field in regions of transition between the urban and rural areas in the state of Tocantins, Brazil, (11°40′55.7″ latitude S, 49°04′3.9″ longitude W), where no insecticides have been used for the control of mosquitoes. The insects were maintained in the Entomology Laboratory of the Federal University of Tocantins, Gurupi Campus, according to the methodology described previously 44 . Adult mosquitoes were maintained on a 10% aqueous sucrose solution and the blood of live Wistar rats (Rattus norvegicus albinus).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%